Corporate Governance Deviance - Aguilera, Ruth V.; Judge, William Q.; Terjesen, Siri A. (Academy of Management Review, 2018)
We develop the concept of corporate governance deviance and seek to understand why, when, and how a firm adopts governance practices that do not conform to the dominant governance logic. Drawing on institutional theory, coupled with both the entrepreneurship and corporate governance literature, we advance a middle-range theory of the antecedents of corporate governance deviance that considers both the institutional context and firm-level agency. Specifically, we highlight the centrality of a firm’s entrepreneurial identity as it interacts with the national governance logic to jointly create corporate governance discretion (i.e., the latitude of accessible governance practices) within the firm. We argue that as a firm’s governance discretion increases, it will be more likely to adopt overconforming or underconforming governance practices that deviate from established norms and practices. Moreover, we propose that adopting a deviant corporate governance practice is contingent on the governance regulatory environment and a firm’s corporate governance capacity. We conclude by advancing a new typology of corporate governance deviance based on a firm’s over- or underconformity with the dominant national logic, as well as its entrepreneurial identity motives. This globally relevant study refines and extends comparative corporate governance research and enriches our current understanding of the institutional logics perspective.